Corka czarownicy na hustawce - Stachowicz, Izabela (Warszawa : Krajowa Agencja Wydawnicza, 1992)
Childhood reminiscences of the author's youth in Poland.
In Polish.
Keywords: Stachowicz, Izabela -- Juvenile literature; Poland -- Biography -- Juvenile literature